Pengaruh Kualitas Pelayanan dan Citra Perusahaan terhadap Loyalitas Nasabah pada PT. BPR Sukawati Pancakanti - A.A Putu Jaya Pramana Putra; I Gst Lanang Putu Tantra; Ni Putu Rediatni Giri (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2023)
This study aims to determine the effect of service quality and corporate image on customer loyalty. The population in this study are customers who use bank products 3 years with a sample of 31 respondents. Data analysis used in this research is Multiple Linear Regression, Coefficient of Determination, t-test and f-test. Based on the results of the study it can be seen that; service quality has a positive and significant effect on loyalty. Company image has a positive and significant effect on customer loyalty. Service quality and corporate image together have a significant effect on customer loyalty.